The Political Web - Dahlgren, Peter. author. aut Link
VI, 195 p.
Keywords: As democracy encounters difficulties, many citizens are turning to the domain of alternative politics and, in so doing, making considerable use of the new communication technologies. This volume analyses the various factors that shape such participation, and addresses such key topics as civic subjectivity, web intellectuals, and cosmopolitanism.